2014
DOI: 10.2217/bmm.14.33
|View full text |Cite
|
Sign up to set email alerts
|

Do Plasma Concentrations of Apelin Predict Prognosis in Patients With Advanced Heart Failure?

Abstract: Plasma apelin concentrations do not predict medium to long-term prognosis in patients with advanced HF secondary to left ventricular systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In a previous study, apelin level found to be increased at early and acute stage of HF, but progressively decreased in the advanced stages of the HF. Additionally, its predictive role has been studied in several studies [22,23]. In our study, lower serum levels of apelin were observed in the HF patients in parallel with the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, apelin level found to be increased at early and acute stage of HF, but progressively decreased in the advanced stages of the HF. Additionally, its predictive role has been studied in several studies [22,23]. In our study, lower serum levels of apelin were observed in the HF patients in parallel with the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…66 However, despite this significant reduction, plasma apelin concentrations were not predictive of outcome in these patients. 70 In contrast to those findings, no significant difference in plasma apelin levels was noted between 65 patients with stable dilated cardiomyopathy (97% NYHA I/II) and normal control subjects. 71 Whether or not this disparity reflects the differing levels of disease severity in the patient groups can only be speculated at this time.…”
Section: Effect Of Hf On the Apelin-apj System In Humansmentioning
confidence: 60%
“…Some of these have been reported to play important roles in the carcinogenesis of HCC. For instance, apelin has been associated with many human diseases such as type 2 diabetes, 15 advanced heart failure, 16 and obesity. 17 Apelin is a novel angiogenic factor that functions like VEGF to promote angiogenesis and tumor growth.…”
Section: Discussionmentioning
confidence: 99%